Pemberdayaan Pemuda Desa: Motivasi Pemerintah Ululere Kecamatan Bungku Timur Kabupaten Morowali - Nurhamni Nurhamni; Ilham Ilham (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2020)
This research the aim to know the motivation of village government in empowering youth in Ululere Village, East Bungku District, Morowali Regency. This type of research is qualitative descriptive research. The number of informants involved in this research is as many as five informants, while the technique of determining the informant using Purposive technique. In addition, in data collection techniques in this study through observation, interview, and documentation. Based on the results of the research note that the motivation of village government in empowering the youth in Ululere Village, East Bungku District, Morowali Regency is considered to have been running well enough, where all aspects used as a reference, such as encouraging humans to act, determine the direction of deeds and selecting deeds are judged to run quite well . However, these activities are still constrained by the lack of youth participation in the village to be involved in the empowerment activities organized by the youth organization in the village. So this becomes a homework for the village government to make more efforts to encourage the entire community, especially youth to participate actively in these activities.